INDUCTION OF ABACA BANANA ROOTS BY IN VITRO USING KINDS OF MEDIA AND THIAMIN - Rina Srilestari; Suwardi Suwardi (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2020)
Abaca is a type a banana with high economic value with it stem fiber used in textile and paper industries. As a superior commodity, its number is relatively limited, with the need of a largeplanting area to meet the high market demand. The aim of the research was to observe the abaca banana explants response to various media and Thiamin. The experiment was done at Biotechnology laboratory, UPN “Veteran” Yogyakarta. Treatments were arranged in completely randomized design with 2 factor. The first factor is the growing media: Murashige & Skoog, a half Murashige & Skoog media, Vacint & Went Media and the second factor is the Thiamin concentration: 2 mg/L; 3 mg/L; 4 mg/mL.The results showed there is an interactions on the parameters of planlet height, number of lenghth of root in the combination of Murashige and Skoog and thiamin 3 mg/L medium. Murashige and Skoog medium produced the highest fresh weight and dry weight and Thiamin concentration 3 mg/L produced fresh and dry weight in the highestKey words: abaka, root induction, various media, thiamin